PECULIARITIES OF FORMATION OF LIQUIDITY INDICATORS IN PORTFOLIO MANAGEMENT OF FINANCIAL INSTITUTIONS - Shevchenko, Dmytro (Socio-economic relations in the digital society, 2020)
The article is devoted to the substantiation of theoretical and methodological principles and the development of scientific and practical recommendations on the peculiarities of the formation of liquidity indicators in the portfolio management of financial institutions. The study substantiates the essence of the category "liquidity" and identifies its structure, proves the need for its evaluation. The conditions of low liquidity in developing companies are systematized. Based on statistical materials of the State Statistics Committee of Ukraine, reporting data of the Ministry of Finance of Ukraine, materials of the World Bank, and reports of the World Economic Forum, the efficiency of development of companies of the European Union and Ukraine is analyzed. The article considers the definition of stock market liquidity and the assessment of liquidity in the stock market and the model that takes into account liquidity when building the optimal investment portfolio. The issue of comprehensive assessment of liquidity in the stock market and factors that take into account liquidity in building an optimal investment portfolio are also investigated. The study was conducted using the following methods: analysis and synthesis of scientific papers — when considering the definition of stock market liquidity; economic-statistical and evaluation — in the analysis of statistical data that characterize the liquidity of the market; graphic — for visual presentation of research results; modeling — when building a model that takes into account liquidity risk in portfolio theory. It is substantiated that in order to create a liquid market, the state needs to take the following steps: maintain a competitive market environment; minimize transaction costs; maintain adequate, modern and safe market infrastructure through the introduction of new technologies; maintain the diversity of market participants; maintain political stability in the country; effectively manage debt in a crisis; maintain exchange rate stability; achieve a reduction in inflation; sell state-owned enterprises (privatization); reduce the share of the public sector; maintain a high rate of savings; to support the growth of foreign capital inflows; weaken government regulation and liberalize financial markets; to support the growth of international trade, etc.